1986
DOI: 10.1111/j.1600-0609.1986.tb02318.x
|View full text |Cite
|
Sign up to set email alerts
|

True idiopathic splenomegaly ‐ a distinct clinical entity

Abstract: South Africa 10 asymptomatic young male patients with moderate splenomegaly detected at a routine examination are presented. The history and clinical examination failed to reveal the aetiology of the splenomegaly. Further investigations, including screening for blood dyscrasias, clotting abnormalities and reticuloendothelial abnormalities were likewise unrevealing. Liver biopsies, rectal biopsies for bilharzia and bone marrow aspirates for Gaucher's Disease were found to be normal. Serology for malaria and Ebs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Ebaugh and McIntyre (1967) detected splenomegaly in 3% of U.S. college freshmen, and found no significant clinical disorder on follow-up (McIntyre and Ebaugh, 1979). Hesdorffer et al (1986) identified 10 young males with mild splenomegaly for which no significant cause was found, although five had IgG antibodies specific for cytomegalovirus. Berris (1966) found 12% of normal postpartum women to have palpable spleens.…”
Section: Splenic Hamartoma (Splenoma)mentioning
confidence: 99%
“…Ebaugh and McIntyre (1967) detected splenomegaly in 3% of U.S. college freshmen, and found no significant clinical disorder on follow-up (McIntyre and Ebaugh, 1979). Hesdorffer et al (1986) identified 10 young males with mild splenomegaly for which no significant cause was found, although five had IgG antibodies specific for cytomegalovirus. Berris (1966) found 12% of normal postpartum women to have palpable spleens.…”
Section: Splenic Hamartoma (Splenoma)mentioning
confidence: 99%